Hyperglycemia-induced oxidative stress exacerbates mitochondrial apoptosis damage to cochlear stria vascularis pericytes via the ROS-mediated Bcl-2/CytC/AIF pathway - Tian-feng Shi; Zan Zhou; Wen-jun Jiang; Tian-lan Huang; Jun-qiang Si; Li Li (Taylor & Francis Group, 2024)
Objectives: Diabetes is closely linked to hearing loss, yet the exact mechanisms remain unclear. Cochlear stria vascularis and pericytes (PCs) are crucial for hearing. This study investigates whether high glucose induces apoptosis in the cochlear stria vascularis and pericytes via elevated ROS levels due to oxidative stress, impacting hearing loss.Methods: We established a type II diabetes model in C57BL/6J mice and used auditory brainstem response (ABR), Evans blue staining, HE staining, immunohistochemistry, and immunofluorescence to observe changes in hearing, blood-labyrinth barrier (BLB) permeability, stria vascularis morphology, and apoptosis protein expression. Primary cultured stria vascularis pericytes were subjected to high glucose, and apoptosis levels were assessed using flow cytometry, Annexin V-FITC, Hoechst 33342 staining, Western blot, Mitosox, and JC-1 probes.Results: Diabetic mice showed decreased hearing thresholds, reduced stria vascularis density, increased oxidative stress, cell apoptosis, and decreased antioxidant levels. High glucose exposure increased apoptosis and ROS content in pericytes, while mitochondrial membrane potential decreased, with AIF and cytochrome C (CytC) released from mitochondria to the cytoplasm. Adding oxidative scavengers reduced AIF and CytC release, decreasing pericyte apoptosis.Discussion: Hyperglycemia may induce mitochondrial apoptosis of cochlear stria vascularis pericytes through oxidative stress.